2021
DOI: 10.1016/j.jot.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The construction of a novel xenograft bovine bone scaffold, (DSS)6-liposome/CKIP-1 siRNA/calcine bone and its osteogenesis evaluation on skull defect in rats

Abstract: Background Xenograft bone scaffolds have advantages such as mechanical strength, sufficient source and safety. Combined with siRNA properly targeting CKIP-1, a negative regulator of osteogenesis, may contribute to the repair result of calcine bone alone. Methods Herein, we constructed a novel xenograft bovine bone scaffold namely (DSS)6-liposome/CKIP-1 siRNA/calcine bone, the characteristics of which were investigated by confirming the effect of (DSS)6-liposome, observi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…RT-qPCR was conducted as previously described. 46 Briefly, total RNA from each sample was extracted using TRIzol reagent and reverse transcribed with a Script™ Reverse Transcription Kit (A276A, Promega). SYBR Green qPCR Master Mix (B21202, Bimake) was used for RT–qPCR with a 7500 real-time PCR instrument (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR was conducted as previously described. 46 Briefly, total RNA from each sample was extracted using TRIzol reagent and reverse transcribed with a Script™ Reverse Transcription Kit (A276A, Promega). SYBR Green qPCR Master Mix (B21202, Bimake) was used for RT–qPCR with a 7500 real-time PCR instrument (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…SCs labeled by IOPNs can migrate and home to specific sites in response to magnetic fields. It has been disclosed that the presence of SPIONs confers special magnetic properties to PLGA microspheres, which greatly promote the proliferation, migration, and osteogenic differentiation of BMSCs under the influence of external magnetic fields (Zhao et al, 2021). Moreover, the combination of pulsed electromagnetic fields (PEMF) and SPIONs were synergistic role in promoting the directional migration and osteogenic differentiation of BMSCs (Wu et al, 2018).…”
Section: Stem Cells Migration and Homingmentioning
confidence: 99%
“…3D printing technology for composite scaffolds is another commonly used method whose versatility makes it increasingly important in bone regeneration. The study found that IONPs-rich PLGA copolymer scaffolds prepared through the layer-by-layer assembly by 3D printing technology promoted cell adhesion and enhanced osteogenesis of rat BMSCs (Han L. et al, 2021). Saraiva's group (Saraiva et al, 2021) used 3D printing to create a polylactic acid platform loaded with HA, IONPs, and an antibiotic (minocycline) with tunable properties and a multi-stimulus response.…”
Section: The Role Of the Composite Scaffoldsmentioning
confidence: 99%
“…Bone defect as a result of diseases and traffic accidents is one of the most detrimental medical issues due to its high disability and morbidity [ 1 ], of which the orthopedic surgery cases have been predicted globally to reach over 28 million by 2022 [ 2 ]. Conventional treatment for large bone defects is to use bone grafts harvested from the patients or compatible donors for bone fixation and regeneration, however, this common practice is still associated with several limitations, including unmatched shape, disease transmission, and additional morbidity [ [3] , [4] , [5] , [6] ]. Various kinds of synthetic biomaterials have been explored as bone grafts, e.g.…”
Section: Introductionmentioning
confidence: 99%